ANALISIS DALAM MENERAPKAN MEDIA INTERAKTIF WORDWALL PADA PEMBELAJARAN TEMATIK DI KELAS III SDN WONOTINGAL - Tri Antika Indah Listiana; Sri Suneki; Joko Suliyanto; Lilik Poncowati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the analysis in applying wordwall interactive media to thematic learning in grade 3 SDN Wonotingal. This type of research uses a qualitative approach, where this research is as it is and produces descriptive data, the source of this research data is in the form of observation sheets and interviews that have been conducted in schools with grade 3 teachers. The results of this study indicate that using interactive wordwall media can help teachers in preparing material to make it more interesting and easy for students. Apart from that, wordwall interactive media also makes it easy for novice users with all the feature menus that are displayed. In implementing this interactive media there are obstacles faced, namely there are inadequate facilities and infrastructure, lack of mastery of teachers who do not master this interactive media technology, and there are students who do not yet have awareness of the importance of paying attention to the teacher when giving subject matter so that they can interfere with the learning process. learning.